2020
DOI: 10.1089/bfm.2019.0193
|View full text |Cite
|
Sign up to set email alerts
|

Physician Mothers and Breastfeeding: A Cross-Sectional Survey

Abstract: Objectives: To explore infant-feeding intentions and behavior of physician mothers as well as their breastfeeding enablers and obstacles. Study Design: A cross-sectional online survey was conducted among female physicians with at least one biological child recruited through the Academy of Breastfeeding Medicine. The main outcomes were duration of exclusive breastfeeding (EBF) and duration of any breastfeeding (BFD). We determined predictors of EBF and BFD. Results: The 570 participants reported intention to br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 24 publications
4
32
0
1
Order By: Relevance
“…reached their 12-month breastfeeding goal. 13 In our study, the frequency of exclusive breastfeeding for the first 6 months was similar to the data of these studies but the frequency of total breastfeeding for ≥12 months was found to be higher. Our results were similar to those reported for Turkish society and other Turkish mothers working as physicians.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…reached their 12-month breastfeeding goal. 13 In our study, the frequency of exclusive breastfeeding for the first 6 months was similar to the data of these studies but the frequency of total breastfeeding for ≥12 months was found to be higher. Our results were similar to those reported for Turkish society and other Turkish mothers working as physicians.…”
Section: Discussionsupporting
confidence: 89%
“…The rate of supportive attitude from coworkers to breastfeeding was lower compared to the literature studies conducted with healthcare professionals. 10,13,25 The low rate of coworker support for breastfeeding mothers in family medicine, which is the cornerstone of breastfeeding support for society, is an important finding that needs to be further examined. Sattari et al 13 determined that the physician mothers receiving coworker support had a longer duration of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Education level, previously having breast feeding experience, having more than two public health nurse visits, and having a positive infant feeding attitude were independently and statistically significantly associated with breast feeding. 9 Interventions promoting behavior change with regards to breastfeeding should focus on dispelling the beliefs and practices. 10 The present study showed that 79.3% had satisfactory knowledge, 54.8% had satisfactory attitude and only 44.5% had satisfactory practice with religion and socio-economic status being statistically significant factors influencing knowledge attitude and practice.…”
Section: Discussionmentioning
confidence: 99%